DEVELOPMENT OF INTEGRATED ISLAMIC CURRICULUM IN AN INTEGRATED ISLAMIC SCHOOL NETWORK TO IMPROVE THE QUALITY OF EDUCATION IN SMA IT NUR HIDAYAH KARTASURA - Handayani, Dwi Utari; Istanto, Istanto (Muhammadiyah University Press, 2019)
Curriculum is a school-designed activity to provide a variety of experiences to students, both inside and outside the classroom. The curriculum is not only identic with the subject matter, but all activities designed by the school to develop the student's self capacity are also included in the curriculum. Education is a process that must be developed according to human needs. Human needs have always evolved every time the rapid growth of the times. In the development of the school curriculum, the curriculum is integrated with the national curriculum and the unified Islamic curriculum, which is where the school has developed both curriculum since 2015 and refers to the Qur'an and As-Sunnah.This research examines how the curriculum development in IT Nur Hidayah Kartasura High School in improving the quality of education and integration of national and Islamic curriculum integrated in the SMA IT Nur Hidayah Kartasura. This research aims to describe the problem of curriculum development and what is integrated national and Islamic curriculum to improve the quality of education in IT Nur Hidayah Kartasura High School.This research is a type of qualitative research, taking place at SMA IT Nur Hidayah Kartasura. In data collection, the authors conduct field studies with data collection methods in the form of interviews, observations and documentation. The analysis of data carried out using the deductive method i.e. departing from the theoretical foundation is then adjusted to be reduced to a more detailed data cause. Based on the results of research conducted by researchers, it can be concluded that SMA IT Nur Hidayah has been conducting curriculum development well and correctly and in accordance with the procedures where the school established a curriculum development team ( TPK). In the formation of TPK need preparation of human resources which include: Skills for training, curriculum documents planning, and the implementation of the curriculum. So in the election of this TPK an educator must be competent. In addition, the writing that was done at SMA IT Nur Hidayah has implemented two curricula in a single curriculum, namely the National Curriculum and integrated Islamic Curriculum (IT). The national curriculum or 2013 curriculum has been referring to scientific approaches designed in such a way that learners can be 5M (observe, formulate problems, file or formulate hypotheses, collect data, communicate). Therefore students are more active in demand. While the integrated Islamic curriculum is based on the Qur'an and As-Sunnah which is where this approach is not only the earthly only Melanikan to Ukhrowi or the hereafter.Curriculum is a school-designed activity to provide a variety of experiences to students, both inside and outside the classroom. The curriculum is not only identical with the subject matter, but all activities designed by the school to develop the self-capacity of students. Education is a process that should be developed according to human needs. Human needs have always evolved every time the rapid growth of the times. In the development of the school curriculum to develop an integrated Islamic curriculum that joins the integrated Islamic School Network (JSIT), where the school has developed the curriculum since the year 2015 and refers to the Qur'an and As-Sunnah.